In-pipe axial pico-hydraulic tailored turbine design: A novel approach using a dimensionless design chart. (15th December 2021) - Vivas, Abraham; Viedma, A.; S. Kaiser, A.
Highlights: New dimensionless approach is presented to design pico-hydraulic axial turbines. Novel flow-to-head factor used to obtain a compact dimensionless design chart. In-pipe tubular torpedo shaped turbines with simple blades are obtained. Simulated designed example turbine achieves 65 % hydraulic efficiency. Abstract: Energy consumed by the water industry is not negligible and improvements on energy efficiency in water distribution networks are still needed. This work aims to provide a new approach to design tailored torpedo shaped in-pipe axial pico-hydraulic turbines for the recovery of energy in water distribution networks. Simple straight untwisted blades with arc of circles profiles are imposed to simplify manufacturing. Ideal flow bi-dimensional cascade theory with Weinel isolated airfoil to cascade correlations are used as compromise between accuracy and simplicity. From it, a dimensionless design chart is build. A novel flow-to-head factor is chosen as main dimensionless factor to simplify stator analysis and obtain a more compact chart. From five usual input design parameters, choosing the value of three, and letting two of them to vary allows the trace of a space of all optimal designs. From this space, a turbine or family of turbines can be obtained. A design example on the same conditions as a experimentally tested turbine found in the literature was carried over and simulated with OpenFOAM open source library. A mesh parametric study for numerical validation purposes is realized. Discretization uncertainty found for the selected mesh was about one point for the hydraulic efficiency. The designed and simulated turbine showed a maximum hydraulic efficiency of 65 % . The presented non-dimensional approach proved to be useful to design efficient tailored simple pico-hydraulic turbines for energy recovery in distribution water networks, relaying on one design chart.